2016
DOI: 10.1111/codi.13158
|View full text |Cite
|
Sign up to set email alerts
|

Increased 30‐day mortality in patients with diabetes undergoing surgery for colorectal cancer

Abstract: Preexisting diabetes was associated with a higher short-term mortality in patients with CRC. No association between the type of antidiabetic medication and short-term mortality could be shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
14
1
1
Order By: Relevance
“…In addition this study does not corroborate with Yeh et al, [14], which found that diabetes independently increases the perioperative risks to patients. To further conflict with these results, Fransgaard et al, [15] found no increased perioperative morbidity, but an increase of 17% in 30-day mortality in patients with diabetes. By including more variables into our multivariate analysis, we have been thorough in removing possible confounding factors in addition to ensuring that all surgeries were conducted with a specialist colorectal surgeon.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition this study does not corroborate with Yeh et al, [14], which found that diabetes independently increases the perioperative risks to patients. To further conflict with these results, Fransgaard et al, [15] found no increased perioperative morbidity, but an increase of 17% in 30-day mortality in patients with diabetes. By including more variables into our multivariate analysis, we have been thorough in removing possible confounding factors in addition to ensuring that all surgeries were conducted with a specialist colorectal surgeon.…”
Section: Discussionmentioning
confidence: 96%
“…Yeh et al, [14] used a nationwide database from Taiwan comparing diabetic to non-diabetic patients and found that patients with diabetes were at higher risk of perioperative mortality, as well as at higher risk of acute renal failure and acute myocardial infarction. Fransgaard et al, [15] found an increased 30-day mortality for patients with diabetes but no increase in post-operative complications. Anand et al, [16] using the United States Nationwide Inpatient sample database, concluded that patients with diabetes had a 23% lower mortality and fewer perioperative complications compared to patients without diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis has reported the effect of DM on CRC prognosis[5], but since 2013, a series of large-scale long-term cohort studies had comprehensively reported the outcome effect estimates on the relationship between DM and CRC prognosis, and their results were still consistent[620]. For example, in overall survival (OS) of CRC, several studies found that DM showed a significant decreased risk in OS[6, 7, 1214, 17], and others found no link[811, 15, 16, 1820]. The data from these studies has also allowed us to evaluate the relationship between DM and CRC prognosis more accurately.…”
Section: Introductionmentioning
confidence: 99%